Enhancing Plasma Electrolytic Oxidation (PEO) Coatings on Magnesium Alloys: The Critical Role of Surface Pretreatments - Arash Fattah‐alhosseini; Abdelhameed Fardosi; Alireza Askari; Minoo Karbasi; Burak Dikici; Mosab Kaseem (Advanced Materials Interfaces)
Abstract Plasma Electrolytic Oxidation (PEO) is a cutting‐edge method for creating ceramic‐like protective coatings on valve metals like magnesium (Mg), titanium (Ti), or aluminum (Al). These coatings exhibit exceptional wear resistance, corrosion protection, and high‐temperature stability, making them indispensable for applications in biomedical, aerospace, and automotive industries. However, the PEO process alone does not fully determine the quality, effectiveness, and performance of these coatings, the surface preparation of the substrate before coating is equally critical. Proper surface pretreatment is essential for achieving optimal adhesion, microstructure, and uniformity of the coatings. Surface pretreatment techniques such as heat treatment, severe plastic deformation (SPD), laser surface modification, chemical immersion, cold spray deposition, and magnetron sputtering have been widely explored to optimize the interfacial bonding and microstructural characteristics of PEO coatings. Understanding the intricate relationship between pretreatment strategies, substrate properties, and PEO process parameters is key to developing coatings with superior corrosion resistance, mechanical integrity, and defect control. This review provides a comprehensive evaluation of various pretreatment methods applied prior to PEO on Mg alloys, assessing their influence on coating morphology, phase composition, electrochemical behavior, and tribological performance. Furthermore, critical challenges and future research opportunities is identified in this domain, particularly in the development of hybrid pretreatment approaches and multifunctional coatings. By refining these processes, researchers can unlock new pathways for enhancing the durability and functionality of Mg alloys in extreme environments, expanding their industrial applicability.